Design and development automated gripper control for robotic arm - Ong, Rong San (2013)
The gripper is considered an important part of a robot, it has been wisely used in all kinds of all industries to increase the efficiency. Commonly it is designed as a mechanical hand by using the mechanical force in the automation system. It only can manipulate to the similar object, size and shape, because sequence motion is already compiled by a programmer. This makes user hard to manipulate and only can control the gripper manually. Thus to make the gripper can do the work in different conditions, the sensor and control systems are required for development automated gripper. The pressure force and infrared distance sensor use to measure the force and distance, with this device the gripper can contact with the work-piece without deformation. The signal from the sensor will transmit to the computer control by using a close loop system. This type of control system would able to analysis the data for control the position of the gripper. To prevent the object slip down from the gripper, and to grasp various types of object. In addition, the control system would able to control well in gripping force, the gripping force is a contact force per unit gripping are to clamp the object. This can gripper avoid the deformation of the work-piece because of the unconstant gripper force. Visual Basic (VB) programming language will used in the computer control system to control the overall movement of the gripper, because the VB programming ability to show the graphical user interface (GUI), to make the user more easy to control the sequence motion of the gripper. Besides the user also can control the gripper in a short period without using a complex formula to calculate the gripping force. Therefore data were analysed by the computer control system to control the gripping force and motion of the gripper. Through the programming abilities to show out the diagram about the position sensor, thus users can know the overall the condition of the gripper. Contribution gripper can apply to real life not only in the industry, it also can help people reduce the burden in daily life. Therefore the fundamental to design the gripper is important, it can show out the visualize force by using CATIA Finite Element Method (FEM) to the built the structure of the gripper. This can reduce the critical point in a particular area, and improve the reliability and endurance of the gripper. This all aspect must take into consideration to develop the automated gripper, these designs were fulfilled with the basic requirement believe in the future it able to perform multitasking for the robotic arm.